Differential Role of Base Pairs on gal Promoters Strength. Issue 4 (27th February 2015) - Lewis, Dale E.A.; Le, Phuoc; Adhya, Sankar
Abstract: Sequence alignments of promoters in prokaryotes postulated that the frequency of occurrence of a base pair at a given position of promoter elements reflects its contribution to intrinsic promoter strength. We directly assessed the contribution of the four base pairs in each position in the intrinsic promoter strength by keeping the context constant in Escherichia coli cAMP-CRP ( c AMP r eceptor p rotein) regulated gal promoters by in vitro transcription assays. First, we show that base pair frequency within known consensus elements correlates well with promoter strength. Second, we observe some substitutions upstream of the ex-10 TG motif that are important for promoter function. Although the galP1 and P2 promoters overlap, only three positions where substitutions inactivated both promoters were found. We propose that RNA polymerase binds to the − 12T base pair as part of double-stranded DNA while opening base pairs from − 11A to + 3 to form the single-stranded transcription bubble DNA during isomerization. The cAMP-CRP complex rescued some deleterious substitutions in the promoter region. The base pair roles and their flexibilities reported here for E . coli gal promoters may help construction of synthetic promoters in gene circuitry experiments in which overlapping promoters with differential controls may be warranted. Graphical Abstract: Highlights: Base pair frequency of known consensus elements correlates with promoter strength. RNAP binds to − 12T:A as part of double-stranded DNA before the entire − 10 element melts to single-stranded DNA. CCC helps RNAP bind to P1 at the level of both closed and open complex formations. We found that three substitutions in the overlapped area inactivated both P1 and P2 . The − 11 substitutions are the only changes where CCC could not activate P1 .